The NIE intermittent high-intensity running test: a reliable and valid test for assessment of soccer-specific fitness - Mukherjee, S.; Chia, M. (International Journal of Sports Science and Coaching, 2013)
The overall activity pattern of soccer is that of intermittent high-intensity (Int-HINT) type and elite players have a greater repeated high-intensity running capability. Since soccer involves rapidly changing work intensities in an unpredictable manner, tests simulating overall activity pattern in a cyclical sequence have limited practical usefulness in testing of soccer fitness. The primary aim of this study was to develop a laboratory-based protocol to specifically assess the Int-HINT running capability in soccer players.